PENGARUH PENAMBAHAN YEAST (Candida apicola) PADA SOSIS FERMENTASI DAGING DOMBA TERHADAP KUALITAS FISIK, KIMIA DAN AKSEPTABILITAS - Andry Pratama; Roostita L. Balia; Lilis Suryaningsih (Agroindustrial Technology, University of Trunojoyo Madura, 2021)
Lamb is one of the animals livestock that is less desirable for consumption by some people because it has a distinctive flavour that affected it when were eating, called the smell is